THE INFLUENCE OF PERSONAL SELLING, DISTRIBUTION AND PROMOTION CHANNELS ON CONSUMER BUYING INTEREST IN MULIA TILE CERAMIC PRODUCTS AT PT SURYA ASIA ABADI PEKANBARU - Junaedi, Achmad Tavip; Sofyanto, Sofyanto; Renaldo, Nicholas; Suhardjo, Suhardjo; Suharti, Suharti; Suyono, Suyono; Hutahuruk, Marice Br; Haristan, Meiviana (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This research aims to analyze the influence of personal selling, distribution channels and promotions on consumer buying interest. This research was carried out at PT. Surya Asia Abadi Pekanbaru with unknown population. With the Roscoe approach, the sample was set at 100 people. Data analysis uses multiple linear regression. The research results show that personal selling has a positive and significant influence on consumer buying interest, in addition distribution channels have a positive and significant influence on consumer buying interest and promotions have a positive and significant influence on consumer buying interest in Mulia Tile ceramic products at PT Surya Asia Abadi in Pekanbaru. The management of PT Surya Asia Abadi in Pekanbaru is expected to be able to increase personal selling to each of its consumers, especially in interacting with consumers who come directly to make purchases.